Kebijakan Perlindungan Lingkungan dan Dampaknya terhadapSektor Pariwisata Di Kota Gorontalo - Nirma Abdullatif (CV. ITTC INDONESIA, 2023)
The Hajj and Umrah Guidance Group, hereinafter abbreviated to KBIHU, is a group that provides Hajj and Umrah guidance that has received permission from the Government. The presence of KBIHU really helps the government in providing services to prospective pilgrims who want to perform the Hajj or Umrah properly and perfectly according to the guidance of the Shari'a. KBIHU An-Nabawiy Medan, which has been established since 2005 in the city of Medan, consistently provides guidance on the Hajj and Umrah (manasik) pilgrimages every year. In carrying out its activities, KBIHU An.Nabawiy Medan carries out organizational communications at KBIHU to form the readiness of prospective pilgrims. The aim of this research is to find out how organizational communication at KBIHU An-Nabawiy Medan is carried out in shaping the readiness of prospective pilgrims in the city of Medan. This research was conducted at KBIHU An-Nabawiy Medan using a qualitative method with a descriptive approach, where the author tried to provide a description, explain and interpret the object being studied systematically. The data collection technique uses observation, interviews and documentation techniques, while the technique for determining informants uses purposive sampling techniques, namely the leadership of KBIHU An-Nabawiy, staff and Hajj pilgrims. Based on the research results, it can be concluded that in general organizational communication at KBIHU An-Nabawiy Medan, both internal and external, plays an important role in shaping the readiness of prospective Hajj pilgrims.